Parental Strategies in Instilling Egalitarian Values in Early Childhood (Current Research in Education: Conference Series Journal, 2024)
This article discusses strategies used by parents in an effort to instill egalitarian values in young children. This research reflects the importance of early education that focuses on gender equality. The research method used is a literature review of books, journal articles, and proceedings. The results showed that the most successful parenting strategies included open communication about egalitarian values, positive role models, and educational resources supporting gender equality. This article provides valuable insight for parents and educators in supporting the development of children with strong egalitarian values from an early age. The research results show that the strategy used by